PELATIHAN PERHOTELAN UNTUK MENINGKATKAN PELAYANAN, KUALITAS PELAYANAN DAN KETERAMPILAN KOMUNIKASI MELALUI METODE SIMULASI [HOSPITALITY TRAINING TO IMPROVE SERVICE, QUALITY OF SERVICE, AND COMMUNICATION SKILLS THROUGH THE SIMULATION METHOD] - Cornelia Tjai (Jurnal Teropong Pendidikan, 2021)
This Classroom Action Research (CAR) was conducted to offer solutions for Dapur Solo (DS) Restaurant as the waiters’ service quality and communication skill did not meet expectations: (1) the previous training had been done by the direct supervisor of the waiters; (2) optimal training had never been done, not inline with the training theory and management expectation;(3) no assessment had been used to measure the success of training. This CAR was done in three cycles.  The subjects of this research were seven waiters of DS Jakarta. The data collection was conducted with observations, field notes, written assessments, rubrics and documentations with descriptive qualitative analysis. The result of this research showed: (1) there was an improvement in the learning: there were instructional design, post-training implementation in accordance to the lesson plans, and assessments to measure the success of the training; (2) 86% of the training participants had increased on the quality of service; and (3) 100% of the training participants had increased on communication skills.